The Project "Analysis of Psychological Practice" or: An Attempt at Connecting Psychology Critique and Practice Research - Fahl, Renke; Markard, Morus (Outlines. Critical Practice Studies, 1999)
Using interviews and group discussions, researchers and students from the Free University of Berlin and psychological practitioners work together in a project called ’The Analysis of Psychological Practice’, theoretically based on ’Critical Psychology’. The aim is to find out whether and how practitioners deal with the contradictions between experimental-statistical orientation of traditional academic psychology and the single-case-orientation of psychological practice. Can practitioners relate to ’scientific’ psychology at all? How do they deal with the contradiction that psychological practitioners are expected to cure psychological problems without having the possibility to change objective conditions with reference to which alone psychological problems are understandable? How are ’official’ academic or clinical theories and individual or team-related experiences combined? What can we learn from the explication and development of a ’social-subjective knowledge of the context and contradictions’ of professional practitioners of psychology? We discuss theoretical foundations and problems in the empirical development of the project, and resent - from our workshop - three examples or dimensions of our work: life problems, problems of and alternatives to traditional diagnostics, and common sense normative ideas in the guise of psychological theories.